2019
DOI: 10.1111/jmwh.13009
|View full text |Cite
|
Sign up to set email alerts
|

Using the Technology Acceptance Model to Develop StartSmart: mHealth for Screening, Brief Intervention, and Referral for Risk and Protective Factors in Pregnancy

Abstract: Introduction: Technology decision support with tailored patient education has the potential to improve maternal and child health outcomes. The purpose of this study was to develop StartSmart, a mobile health (mHealth) intervention to support evidence-based prenatal screening, brief intervention, and referral to treatment for risk and protective factors in pregnancy. Methods:StartSmart was developed using Davis' Technology Acceptance Model with end users engaged in the technology development from initial concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…One intervention consisted of a tablet-based screening tool with motivational interviewing prompts that were individually generated based on reported risks. 48 Women interviewed in this study reported feeling that they could better adhere to the treatment guidelines for IPV after using the tablet-based screener. Another intervention was a computer-based screener with a 15-min informational video and prompting card that was given to the provider.…”
Section: Interventions and Outcomesmentioning
confidence: 86%
See 4 more Smart Citations
“…One intervention consisted of a tablet-based screening tool with motivational interviewing prompts that were individually generated based on reported risks. 48 Women interviewed in this study reported feeling that they could better adhere to the treatment guidelines for IPV after using the tablet-based screener. Another intervention was a computer-based screener with a 15-min informational video and prompting card that was given to the provider.…”
Section: Interventions and Outcomesmentioning
confidence: 86%
“…Most interventions took place in prenatal care clinics (n =15), [25][26][27][28][29][30][31][32][33][34]39,40,43,47,48 hospitals (n = 8), [36][37][38][41][42][43]49,50 or primary care clinics (n = 5). 39,45,51,52 Some took place in midwife clinics (n = 3).…”
Section: Settingsmentioning
confidence: 99%
See 3 more Smart Citations